Experimental Investigation of Closed Porosity of Inorganic Solidified Foam Designed to Prevent Coal Fires - Yi Lu; Botao Qin (Advances in Materials Science and Engineering)
In order to overcome the deficiency of the existing fire control technology and control coal spontaneous combustion by sealing air leakages in coal mines, inorganic solidified foam (ISF) with high closed porosity was developed. The effect of sodium dodecyl sulfate (SDS) concentration on the porosity of the foams was investigated. The results showed that the optimized closed porosity of the solidified foam was 38.65 wt.% for an SDS concentration of approximately 7.4×10-3 mol/L. Based on observations of the microstructure of the pore walls after solidification, it was inferred that an equilibrium between the hydration process and the drainage process existed. Therefore, the ISF was improved using three different systems. Gelatin can increase the viscosity of the continuous phase to form a viscoelastic film around the air cells, and the SDS + gelatin system can create a mixed surfactant layer at gas/liquid interfaces. The accelerator (AC) accelerates the hydration process and coagulation of the pore walls before the end of drainage. The mixed SDS + gelatin + AC systems produced an ISF with a total porosity of 79.89% and a closed porosity of 66.89%, which verified the proposed stabilization mechanism.